2018
DOI: 10.3390/v10100552
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Bacteriophages in Enrichment Culture for Improved Prenatal Streptococcus agalactiae Screening

Abstract: Vertical transmission of Streptococcus agalactiae can cause neonatal infections. A culture test in the late stage of pregnancy is used to screen for the presence of maternal S. agalactiae for intrapartum antibiotic prophylaxis. For the test, a vaginal–rectal sample is recommended to be enriched, followed by bacterial identification. In some cases, Enterococcus faecalis overgrows in the enrichment culture. Consequently, the identification test yields false-negative results. Bacteriophages (phages) can be used a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Meanwhile, some studies have shown the efficacy of phages, in vivo, against E. faecalis , using mouse models (Table 1). An intraperitoneal application of phages, significantly rescued mice, when deliberately challenged with the E. faecalis EF14 and E. faecalis VRE2 strains [95]. Similarly, another study has showed that mice treated with different phage doses were protected from the VREF systemic infection, and alleviated the gut microbial imbalance that occurred as a result of infection [91].…”
Section: E Faecalis Phage Therapy In In Vivo Modelsmentioning
confidence: 99%
“…Meanwhile, some studies have shown the efficacy of phages, in vivo, against E. faecalis , using mouse models (Table 1). An intraperitoneal application of phages, significantly rescued mice, when deliberately challenged with the E. faecalis EF14 and E. faecalis VRE2 strains [95]. Similarly, another study has showed that mice treated with different phage doses were protected from the VREF systemic infection, and alleviated the gut microbial imbalance that occurred as a result of infection [91].…”
Section: E Faecalis Phage Therapy In In Vivo Modelsmentioning
confidence: 99%
“…EG-LYS activity was examined using E. faecalis , Enterococcus faecium , Enterococcus avium , and GBS strains isolated from the vaginal swabs in the prenatal GBS screening test ( 17 ). First, EG-LYS activity on peptidoglycan and whole bacterial cells in PBS was analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…We used 5, 30, 5, and 7 strains of E. avium , E. faecalis , E. faecium , and GBS, respectively, which were all isolated from clinical vaginal swabs and identified using mass spectrometry ( 17 ). In the case of GBS strains, the Lancefield B antigens were also tested using a kit (Strept LA “SEIKEN”; Denka Company, Niigata, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting area of research is the application of phages in diagnosis, not to target the bacteria but instead to eliminate common sample contaminations, thus improving the target bacteria recovery and consequently improving detection. Jumpei Uchiyama and colleagues [13] used this approach to remove Enterococcus faecalis from vaginal samples, avoiding the overgrowth of these bacteria during the enrichment phase, allowing for the detection of Streptococcus agalactiae and decreasing the common high number of false negatives observed with vaginal S. agalactiae diagnosis.…”
Section: Applicationsmentioning
confidence: 99%